Fuzzy logic based modeling for Resistance Spot Welding Process. (2017) - Boriwal, L.; Sarviya, R.M.; Mahapatra, M.M.
Abstract: In this paper, a fuzzy logic based model for the Resistance Spot Welding (RSW) process, which is capable to predict RSW responses the nugget size, tensile shear strength, and peel strength. Welding current, weld cycle and electrode pressure are taken as the process variables for RSW process. The experimental results were used to construction a fuzzy logic model to predict the effect of the input variables on the responses. The fuzzy model was validated by number of test cases to establish its adequacy. The error in predicting the outputs for the input data was within acceptable limits indicating the adequacy of the model to be used for complex processes like RSW.